Influence of Product Quality, Promotion, Price, Trust On the Purchase Decision at Alfa Scorpii Rantauprapat - Bella Sastra Dewi; Yudi Prayoga; Bhakti Helvi Rambe (Quantitative Economics and Management Studies, 2022)
This study was conducted to determine and analyze the effect of product quality (X1), promotion (X2), price (X3) and trust (X4) on purchasing decisions (Y). This research design is hypothesis testing using primary data obtained by distributing 100 questionnaires to consumers of Alfa Scorpii RantauPrapat. The measuring scale used is the Likert scale. The data analysis technique used is the multiple linear regression analysis technique of quantitative data using the statistical methods of the statistical sciences package for the social sciences (SPSS). The results of this study conclude that partially and simultaneously there is a significant and positive influence between product quality, promotion, price and trust on purchasing decisions.